Incidence and prevalence of post-stroke insomnia: A systematic review and meta-analysis. (February 2020) - Baylan, Satu; Griffiths, Susan; Grant, Nicola; Broomfield, Niall M.; Evans, Jonathan J.; Gardani, Maria
Summary: Problems with sleep are reported to be common after stroke but the incidence and prevalence of insomnia and insomnia symptoms following stroke is not yet established. The aim of this review was to conduct a systematic review and meta-analysis of the incidence and prevalence of insomnia and insomnia symptoms in individuals affected by stroke. We searched seven main electronic databases to identify studies until September 25, 2018. No studies examining incidence of post-stroke insomnia were identified. Twenty-two studies on prevalence of insomnia or insomnia symptoms including individuals with stroke were included with fourteen studies suitable for inclusion in the meta-analysis. Meta-analysis indicated pooled prevalence of 38.2% (CI 30.1–46.5) with significantly higher prevalence estimates for studies using non-diagnostic tools, 40.70% (CI 30.96–50.82) compared to studies using diagnostic assessment tools 32.21% (CI 18.5–47.64). Greater insomnia symptoms were indicated in those with comorbid depression and anxiety. The prevalence of both insomnia and insomnia symptoms are considerably higher in stroke survivors compared to the general population. Studies investigating the incidence, insomnia symptom profile and changes in insomnia prevalence over time are needed to inform clinical practice and to encourage tailored interventions that consider this symptomatology. PROSPERO registration number CRD42017065670.